125 Assessment of suicidal crisis intervention: how professional practice assessment improves crisis intervention Preliminary results. (23rd September 2015) - Fouldrin, G; Baguelin-Pinaud, A; Houy-Durand, E; Delavenne, H; Guigueno, S; Preterre, P; Samuel, D; Giorno, F; Daric-Bouchaud, C; Protais, Y; Protais, Y; Lefebvre, I; et al.
Abstract : Background: Reduction of suicidal mortality is one of the most important health public challenges in France. The secondary prevention of suicidal attempts could be ameliorated increasing psychiatric and physical examination. A recent Professional Practise Assessment conduced in our hospital has showed that after a suicidal attempt examined in an emergency service in Rouen University Hospital, only three patients out of 10 accepted to be referred to a psychiatric consultation after hospitalisation. A mobile medical unit (composed of a psychiatrist, a psychologist, a nurse and a social worker) has been created to improve links between hospitalisation treatment and ambulatory treatment (82% of patients accepted to be referred to a psychiatric consultation). At the end of this first study we generalised this practise examination. Method: Ten psychiatrists have performed this professional practise assessment to establish how to assure a daily follow up of suicidal patients. A self-evaluation questionnaire has been developed and authenticated using the French consensus conference 'suicidal crisis' (ANAES, October 2000). All patients responding to suicidal crisis criteria have been included during 2 days. Results: 30 questionnaires have been filled in and analysed. 17 men and 13 women (mean of age: 38+/−17 years) have been included. 60% met DSM IV criteria for depressive disorders (major depressive disorder, dysthymia, bipolar disorder and adaptative disorder). 70% of patients have been referred to a psychiatric consultation (56 had an appointment with the psychiatrist). Appointment with general practitioner never appeared. 93% of patients could have a psychological examination and 86% could meet a social worker. 86% of patients go back home with a family member. These results have been analysed and modifications of our practices have been suggested (increase appointment with general practitioner for example). Contexte: La problématique suicidaire reste un important problème de santé publique en France. La prévention des récidives secondaires des suicidant passe par une amélioration de l'observance des soins. Une première EPP effectuée sur notre unité intersectorielle de suicidologie a montré qu'après une tentative de suicide hospitalisée au urgences de notre CHU, près de 7 patients sur 10 ne se rendent pas au rendez vous proposé avec le psychiatre de leur secteur. La conduite d'amélioration qui a consisté à assurer une continuité de la prise en charge intra et extra hospitalière du patient suicidant, par une équipe mobile multidisciplinaire (psychiatre, psychologue, infirmière et assistante sociale), a montré une augmentation de l'observance (82% de premiers RDV honorés vs 34%). Au terme de cette évaluation des pratiques nous avons généralisé l'évaluation à l'ensemble des prises en charges de patients suicidants à l'ensemble des 10 secteurs de notre établissement. Méthode: Cette EPP est menée sur notre CHS par 10 praticiens hospitaliers afin d'évaluer les prises en charge habituelles des patients en crise suicidaire. Les critères évalués sont ceux de la conférence de consensus "la crise suicidaire : reconnaître et prendre en charge" (ANAES; octobre 2000). Une grille d'auto-évaluation reprenant ces critères a été formalisée et validée. Tous les patients non hospitalisés répondant aux critères de crise suicidaire ont été inclus sur une période de 2 jours. Résultats: 30 grilles ont été renseignées et ont fait l'objet d'une analyse. 17 hommes et 13 femmes (âge moyen 38 +/- 17 ans) ont été inclus. 60% répondaient aux critères DSM IV de troubles de l'humeur (EDM, Tb Bipolaire, Dysthymie et Tb adaptation). A la sortie de l'hôpital, 70% des patients sont orientés vers un psychiatre (dont 56% avec RV pris). L'orientation vers le médecin traitant n'est jamais formalisée. 87% des patients peuvent rencontrer une assistante sociale et 93 % une psychologue. 86 % des patients rentrent accompagnés au domicile. Ces résultats ont été discutés et des modifications des pratiques (formalisation du contact avec le médecin traitant par exemple) ont été proposées. Une prochaine évaluation est programmée afin de mesurer les améliorations de prise en charge.